SEJARAH PERANG SALIB DAN DAMPAKNYA TERHADAP PERKEMBANGAN PERADABAN ISLAM - Amrullah, Wahdaniya (AL-URWATUL WUTSQA: Kajian Pendidikan Islam, 2022)
AbstractThis study aims to describe the history of the crusade and its impact on the development of Islamic civilization. The Crusades were a series of religious wars for almost two centuries as a reaction of European Christianity against Islam. This war happened, because a number of Christian cities and holy places were occupied by Islam since 632 AD. The Christian military used the cross as a symbol to show that this war was holy and aimed at liberating the holy city of Baitul Maqdis (Jerusalem) from Muslims / To show that the war was true -true holy war, all Western fleets and troops leaving for the battlefield must wear the attribute of the cross, whether worn on the sails of their boats, on their flags, starting from the team flags and troop flags, shields, armor, and various other equipment. The crusade that took place around the land of Jerusalem, eventually penetrated into a wide area that took place around 1096-1291M. The focus of the study in this paper is (1). What is the history of the crusades (2). How is the periodization of the crusade (3). What is the impact of the crusade on the European world of the Islamic world. This study finds that the crusades were the result of the birth of expansionism in Europe as was the effort undertaken by Seljuq against the Byzantine Empire. In the expansionary movement carried out by Alp Arselan was the manzikart event, in 464 H, Alp Arselan's army with a strength of 15,000 soldiers defeated the Roman army which numbered 200,000 people. This incident planted the seeds of enmity and hatred among Christians towards Muslims. This hatred increased after the Seljuq dynasty seized Baitul Maqdis in 471 H from the rule of the Fathimiyah dynasty based in Egypt. The Seljuq rulers set rules for Christians who wanted to make pilgrimages there. The regulations were felt to be very difficult for them. In order to gain the freedom of pilgrimage to the Christian holy land, Pope Urban called on the Christians in Europe to wage a holy war. The crusade had several important consequences for world history. The impact of the crusade on the development of Islamic civilization was that the Islamic world experienced setbacks in all areas of life. Incident after incident happened to the Islamic world as if it would not stop, both in Andalusia, Baghdad, Jerusalem and other Islamic countries. Even though the Muslims succeeded in defending their areas from the crusaders, the losses they suffered were enormous, because the Islamic world was hit by various kinds of crises, namely the crisis of religion, state politics, social economy, education and culture. These losses resulted in the political power of the Islamic Ummah becoming weak. In such conditions they are not united but even divided. Keywords ; Crusades, Islamic Civilization